2018
DOI: 10.1377/hlthaff.2017.1028
|View full text |Cite
|
Sign up to set email alerts
|

Community Benefit Spending By Tax-Exempt Hospitals Changed Little After ACA

Abstract: Provisions of the Affordable Care Act (ACA) encouraged tax-exempt hospitals to invest broadly in community health benefits. Four years after the ACA's enactment, hospitals had increased their average spending for all community benefits by 0.5 percentage point, from 7.6 percent of their operating expenses in 2010 to 8.1 percent in 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 7 publications
1
94
1
Order By: Relevance
“…Nikpay, Buchmueller, and Levy found that early Medicaid expansion in Connecticut resulted in more Medicaid discharges, but no change in uncompensated care (9). The only nationwide study of the ACA's effect on community benefit spending found a modest increase in total spending, from 7.6 to 8.1% of operating expenses, from 2010 to 2014, but no effect on community health spending (40). And yet, in an analysis of just teaching hospitals, Alberti, Sutton, and Baker found between 2012 and 2015, charity care decreased by 16.7% but total spending increased 20.1% (97).…”
Section: Spending and Finance: Relationshipsmentioning
confidence: 99%
“…Nikpay, Buchmueller, and Levy found that early Medicaid expansion in Connecticut resulted in more Medicaid discharges, but no change in uncompensated care (9). The only nationwide study of the ACA's effect on community benefit spending found a modest increase in total spending, from 7.6 to 8.1% of operating expenses, from 2010 to 2014, but no effect on community health spending (40). And yet, in an analysis of just teaching hospitals, Alberti, Sutton, and Baker found between 2012 and 2015, charity care decreased by 16.7% but total spending increased 20.1% (97).…”
Section: Spending and Finance: Relationshipsmentioning
confidence: 99%
“…7 A 2018 study 8 showed that tax-exempt hospitals did not increase their community benefit spending from 2012 to 2014, although another 2018 study 9 found that teaching hospitals did increase overall community benefit spending from 2012 to 2015. Using hospital tax filings through 2014, Young et al 10 found small decreases in charity care and little change in unreimbursed Medicaid programs as a proportion of hospital spending on community benefit. In follow-up work, Young et al 11 found preliminary evidence that decreases in uncompensated care were partially offset by increases in unreimbursed Medicaid spending during the first year of Medicaid expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Neither the Internal Revenue Service nor the Affordable Care Act mandate a dollar amount or percentage of operating budget that not-for-profit hospitals are required to allocate to their community health improvement projects. Indeed, it has been estimated that nationally only about five percent of community benefit dollars are allocated to community health improvement programs (29). Although a large figure when aggregated nationally, locally, the modest scope of such funds can limit their impact, particularly when viewed in the context of longstanding, unmet community needs.…”
Section: Planning For Sustainable Impactmentioning
confidence: 99%